Effects of five levels of dietary electrolyte balance on growth, carcass characteristics and blood serum metabolites of guinea pig (Cavia porcellus) - Paredes, Manuel (2021)
A study was carried out to determine the effects of dietary electrolyte balance (BED) on the productive performance, carcass characteristics and blood metabolites of guinea pig in an experimental farm in Cajamarca, Peru. In total, 150 male guinea pigs distributed in five treatments with five levels of BED: 100, 200, 300, 400 and 500 mEq/kg. Each treatment had six repetitions and each repetition with five guinea pigs/pen. The guinea pigs consumed concentrated feed for 42 days. At the end of the experimental period, six guinea pigs per treatment were slaughtered to determine the carcass yield, relative weights of the viscera and concentration of blood metabolites. Differences (p<0.05) were found in final body weight, body weight gain, and feed conversion index in favour of guinea pigs with BED of 300 mEq/kg. There were no significant differences between treatments in carcass characteristics or in blood metabolite values, except creatinine. According to the results of this study, guinea pig could be fed 300 mEq/kg of BED, with satisfactory growth results.